ROLE OF AKSI CEPAT TANGGAP (ACT) INDONESIA IN PROVIDING ASSISTANCE TO VICTIMS OF CONFLICT IN SYIRIA IN 2015-2020 - Ali Syahbansa; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to see how the role played by Aksi Cepat Tanggap (ACT) of Indonesia in providing assistance to victims of conflict in Syria and what ACT has provided to help the humanitarian crisis that occurred. The humanitarian crisis that occurred in Syria, has had fatal consequences for various state actors or what is commonly called Non-Governmental Organizations (NGOs), one of which is ACT Indonesia. This study uses a pluralism perspective. Pluralists believe that a successful country is the only actor in the international world. This research is also guided by the theory of Transnational Activism and the concept of the Transnational Advocacy Network. The method used is a qualitative method. Data interview techniques and literature study from several journals, books, documents and websites.The research shows ACT's ability to build international networks such as collaborating with NGOs and local organizations so that ACT is able to play a role in providing humanitarian assistance to the country it is aiming for, in this case the Syrian state. Then ACT Indonesia took action against the victims of the victims by executing the programs that had been made and explaining something related to ACT Indonesia to help victims of conflict in Syria.The results of this study concluded that ACT Indonesia has the ability to build international networks so that ACT is able to provide assistance to victims of conflict in Syria. Keywords: ACT Indonesia, Conflict, Humanitarian Crisis, Syria, NGO,                         Transnational, Advocacy